THE FRAMEWORK OF TEACHING LEARNING PROCESS OF INDONESIAN NATIONAL QUALIFICATION IN PRIVATE COLLEGE - Chontina Siahaan; Hendry Sinuraya; Donal Adrian (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2018)
The Indonesian national qualification the education system is still relatively new, Universitas Kristen Indonesia but as educators, were required to be able to exercise a marksman in conveying the, learning attractive easy to understand and give the opportunity for message receiver to express his response to a clarification on a subject discussed. A research paradigm is constructive. The kind of research is qualitative. The result showed that strategy lecturers in conveying a message or material college-based Indonesia national qualifications framework in Universitas Kristen Indonesia do with how to explain back material that has delivered, use simple sentences and give a case that up to date.